Crusted Scabies in an HIV-Infected Patient - Trigo, Diva (2018)
HIV predisposes infected patients to multiple skin diseases that frequently exhibit atypical clinical presentations. The authors report the case of a 57-year-old man with severe HIV-related immunosuppression who developed a generalized pruritic dermatosis during prolonged hospitalization. Taking into account the patient’s status, his complaints and distribution of lesions, diagnosis of scabies was considered, although lesions were not typical and there was no suggestive epidemiological context. Two treatments with a benzyl benzoate lotion induced only transient improvement. Only a second biopsy confirmed hyperinfestation with Sarcoptes scabiei. Complete recovery followed treatment with ivermectin. The authors present a brief review of some particular aspects regarding diagnosis and treatment of crusted scabies.